2015
DOI: 10.1093/scan/nsv070
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional error-related processing in female psychopathy

Abstract: Neurocognitive studies of psychopathy have predominantly focused on male samples. Studies have shown that female psychopaths exhibit similar affective deficits as their male counterparts, but results are less consistent across cognitive domains including response modulation. As such, there may be potential gender differences in error-related processing in psychopathic personality. Here we investigate response-locked event-related potential (ERP) components [the error-related negativity (ERN/Ne) related to earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 71 publications
5
31
2
Order By: Relevance
“…We used a full sample of incarcerated individuals with a wide range of PCL-R scores to understand the full range of psychopathic traits and identified PCL-R Total score, Factor 1, and Facet 3 to be positively related to Pe amplitude. Only a single study used a large incarcerated sample though it was a female sample (Maurer, et al, in press ) instead of a male sample. Similar to the male sample presented here, interpersonal-affective traits of psychopathy were related to Pe amplitude, but in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a full sample of incarcerated individuals with a wide range of PCL-R scores to understand the full range of psychopathic traits and identified PCL-R Total score, Factor 1, and Facet 3 to be positively related to Pe amplitude. Only a single study used a large incarcerated sample though it was a female sample (Maurer, et al, in press ) instead of a male sample. Similar to the male sample presented here, interpersonal-affective traits of psychopathy were related to Pe amplitude, but in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…Though treating adult psychopathic individuals has proven difficult (Rice & Harris, 1997), with the current findings and the work with juvenile offenders, hope remains for future interventions in adult offenders with elevated psychopathic traits. Also, sex-related differences should be further delineated considering the recent report in female psychopathy (Maurer, et al, in press ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies examining neural and physiological correlates of psychopathy have reported unique effects specific to each of the two overarching factors (e.g. Anderson et al 2015; Iria & Barbosa, 2009; Juárez, Kiehl, & Calhoun, 2013; Maurer et al 2015; Patrick et al, 1993; Philippi et al, 2015; Steele et al 2016; Wolf et al, 2015). Thus, we examine effects related to PCL-R Total score as well as effects corresponding to the two-factor model.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to stimulus-locked brain measures, response-locked events, such as error-related brain activity, are relatively stable with far fewer trial averages (Maurer et al, in press ; Meyer et al, 2013; Olvet and Hajcak, 2009; Pontifex et al, 2010; Rietdijk et al, 2014). Error processing is often assessed with ERPs and fMRI during a response inhibition task (e.g., Go/NoGo, Stroop, Stop-Signal, Flanker, Wisconsin Card Sorting Task, and Task-Switching), or any variety of speeded, continuous performance tasks likely to produce erroneous responses (for review, see (Niendam et al, 2012).…”
Section: 0 Introductionmentioning
confidence: 90%